Development of Risk Stratification Predictive Models for Cervical Deformity Surgery. (16th November 2020) - Passias, Peter; Ahmad, Waleed; Oh, Cheongeun; Renaud, Lafage; Lafage, Virginie; Hamilton, D. Kojo; Protopsaltis, Themistocles; Klineberg, Eric; Gum, Jeffrey L; Line, Breton G; Hart, Robert A; Bess, Shay; et al.
Abstract: INTRODUCTION: As the field of corrective cervical deformity surgery progresses, surgeons continue to take on more challenging cases. In order to minimize suboptimal postoperative outcomes it is important to develop a tool that allows for proper preoperative risk stratification. METHODS: CD patients≥18 years old with complete baseline(BL) and at least 1 year HRQoL and radiographic data were included. Patients were stratified into two groups based on their outcome from surgery: Revision[Rev] and Major Complication[MC]. Descriptive analysis identified demographics, radiographic parameters, and surgical details. Univariate analysis of preoperative and surgical factors was conducted to determine associations with either of the two outcomes. Stepwise logistic regressions identified surgical, radiographic, and HRQL factors that were associated with Rev or MC. Decision tree analysis established cut-offs for predictive variables. RESULTS: 105 CD patients were included(61.6yrs, 67%F, BMI: 28.4kg/m 2 ). Postoperatively, 20 patients experienced a MC and 17 patients underwent a subsequent Rev. Instrumentation location (LIV: 1.1[1.0-1.3] and UIV: 1.5[1.1-2.1]) was significantly associated with undergoing a Rev after index surgery(all P  < .05). The development of a postoperative MC was significantly associated with BL radiographic pelvic parameters (all <0.05). Predictive modeling incorporating preoperative and surgical factors identified development of a Rev to include: UIV>C3, LIV>T3, C2-T3 SVA<46.7°, C2-C7 SVA>57.6°, CTPA>7.8°, and C2S<60.4 (AUC:0.80). For developing a MC, a model consisting of preoperative and surgical factors included BL EQ5D-VAS<30, TS-CL>59.2°, C2-C7 SVA > 69.1°, C2-T3 SVA < 18.6, Apex C2-C7 SVA >4.25, surgical invasiveness and posterior osteotomies(AUC:0.83). CONCLUSION: Major adverse events are not uncommon following adult cervical deformity correction. Risk stratification models were developed to predict with high accuracy the occurrence of these common significant post-operative events. Revisions were predicted with an accuracy of 80% using a predominance of radiographic variables, while the occurrence of other major complications was also predicted with high reliability utilizing additional baseline HRQoL data, and surgical factors.